SEASONAL VARIABILITY OF CARBON DIOXIDE, SENSIBLE AND LATENT HEAT FLUXES IN FOREST AND PEATLAND ECOSYSTEMS OF NORTH SIBERIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The effects of climate change are particularly pronounced in high-latitude regions, with polar environments showing heightened sensitivity to environmental shifts. Plant responses to these alterations are primarily observable through changes in ecosystem processes, especially in terms of water vapor and CO2 exchange patterns. This research investigated the seasonal patterns of CO2 net ecosystem exchange (NEE) and heat transfer (both sensible and latent) in two Northern Siberian ecosystems: a subarctic palsa mire and a mature larch forest. The investigation, spanning from 2019 to 2023, employed eddy covariance techniques to gather new data on how these ecosystems respond to atmospheric changes. The findings revealed that both sites consistently uptake more atmospheric CO2 than they released, despite fluctuating weather conditions between years. During growing seasons, the palsa mire’s NEE readings ranged between –62.9 and –120.2 gC·m–2 while the larch forest showed values from –63.5 to –83.6  gC·m–2.  The heat flux measurements demonstrated substantial year-to-year variability, which was largely influenced by changes in solar radiation levels and rainfall patterns.
Keywords: carbon dioxide fluxes; latent and sensible heat fluxes; eddy covariance; subarctic palsa mire; larch forest; North Siberia; forest-tundra ecosystem; permafrost